2017
DOI: 10.1002/etc.3773
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the toxic effect of pesticides on honey bee drone fertility using laboratory and semifield approaches: A case study of fipronil

Abstract: Concern about the reproductive toxicity of plant protection products in honey bee reproducers is increasing. Because the reproductive capacity of honey bees is not currently considered during the risk assessment procedure performed during plant protection product registration, it is important to provide methods to assess such potential impairments. To achieve this aim, we used 2 different approaches that involved semifield and laboratory conditions to study the impact of fipronil on drone fertility. For each a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 35 publications
3
24
0
1
Order By: Relevance
“…Drones that were raised in semi-field and laboratory conditions and exposed to fipronil through feeding showed a decrease in quantity of spermatozoa and increased mortality of spermatozoa (Kairo et al 2017). This confirmed earlier research by the same authors had shown that queens inseminated with sperm of fipronil exposed drones had less and less viable spermatozoa stored in their spermatheca (Kairo et al 2016).…”
Section: Sublethal Effects On Reproductionsupporting
confidence: 86%
“…Drones that were raised in semi-field and laboratory conditions and exposed to fipronil through feeding showed a decrease in quantity of spermatozoa and increased mortality of spermatozoa (Kairo et al 2017). This confirmed earlier research by the same authors had shown that queens inseminated with sperm of fipronil exposed drones had less and less viable spermatozoa stored in their spermatheca (Kairo et al 2016).…”
Section: Sublethal Effects On Reproductionsupporting
confidence: 86%
“…Furthermore, queens inseminated with semen collected from fipronil-exposed drones contained sperm with significantly lower viability in their spermathecae compared to those inseminated with drones that were fed the insecticide-free syrup. Similar results were obtained for drones reared in laboratory conditions following exposure to fipronil in the sugar syrup, which experienced significantly lower sperm viability and concentration (Kairo et al 2017a). Interestingly, the same research group found that fipronil interacts with the microsporidian parasite Nosema ceranae and their interaction causes lower drone sperm viability and antioxidant activity compared to untreated drones (Kairo et al 2017b).…”
Section: Effects Of Farmer-applied Insecticidessupporting
confidence: 70%
“…In conclusion, the few studies that have explored the effects of exposure to commonly used systemic insecticides in the food have consistently shown significant negative effects to drone reproductive quality by causing lower sperm viability in laboratory, semifield, and field conditions (Straub et al 2016;Kairo et al 2016Kairo et al , 2017a. Furthermore, the insecticide fipronil seems to synergize with, and exacerbate the severity of, infection with N. ceranae .…”
Section: Effects Of Farmer-applied Insecticidesmentioning
confidence: 91%
“…This is the case of the lady beetle Hippodamia variegata exposed to sublethal concentrations of thiamethoxam [80]. Neonicotinoids can also negatively affect honeybee drone sperm quality [81,82] while fipronil affects drone fertility by inducing a decrease in spermatozoa quantity that is associated with an increase in spermatozoa mortality [83], so these insecticides may ultimately lead to colony failure [84].…”
Section: Toxicity Assessmentmentioning
confidence: 99%